Data Science and Intelligent Computing Techniques 2023
DOI: 10.56155/978-81-955020-2-8-9
|View full text |Cite
|
Sign up to set email alerts
|

Mask R-CNN: A Comparative Study On Improvements In Object Detection And Segmentation

Abstract: Over the years there has been an increasing demand for image recognition as the world is moving towards a digital space. With the increasing demands, the application of Mask RCNN and expanded algorithms based on segmentation and YOLO have seen a major rise in the last 5 years. So the accuracy of the models has improved slightly since most projects take different approaches to the different datasets and have different metrics of Evaluation. By cross-referencing these approaches, a trend is observed that leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Recently, long working distance, low‐power optothermoelectric trapping, and spectroscopic studies of fluorescent nanodiamonds (FNDs) are demonstrated by drop casting the chemically synthesized plasmonic nanostructures such as gold nanosphere and silver nanowire (AgNW) on the glass coverslip instead of lithographically prepared gold film or nanoantennae. [ 136 ] The excitation of an anchored single gold sphere (400 nm) by a 532 nm laser using a low NA objective (0.5) quickly traps the FND at a laser intensity down to 12.2 µW µm −2 . The trapping with AgNW with an average diameter of 350 nm requires a minimum intensity of 85 µW µm −2 when the laser polarized along the nanowire to excite the plasmons.…”
Section: Plasmonic Nanostructures‐assisted Optothermal Manipulation O...mentioning
confidence: 99%
“…Recently, long working distance, low‐power optothermoelectric trapping, and spectroscopic studies of fluorescent nanodiamonds (FNDs) are demonstrated by drop casting the chemically synthesized plasmonic nanostructures such as gold nanosphere and silver nanowire (AgNW) on the glass coverslip instead of lithographically prepared gold film or nanoantennae. [ 136 ] The excitation of an anchored single gold sphere (400 nm) by a 532 nm laser using a low NA objective (0.5) quickly traps the FND at a laser intensity down to 12.2 µW µm −2 . The trapping with AgNW with an average diameter of 350 nm requires a minimum intensity of 85 µW µm −2 when the laser polarized along the nanowire to excite the plasmons.…”
Section: Plasmonic Nanostructures‐assisted Optothermal Manipulation O...mentioning
confidence: 99%
“…Reproduced with permission. [87] Copyright 2023, Optica Publishing Group. f) (top left)Active colloidal tweezer(ACT) design with dielectric rod and plasmonic silver nanodisk, (top right) Dynamic manipulation of trapped particles with ACT.…”
Section: Colloidal Nd Manipulation Schemes and Related Demonstrationsmentioning
confidence: 99%
“…A similar approach in Figure 5e was applied, the Opto-thermo-electric (OTE) technique facilitated by surfactant, where the same 532 nm laser was used for resonant excitation of drop-casted Ag nanowires/Au nanoparticles for trapping and exciting NDs. [87] The force due to OTE is higher compared to optical trapping; hence less laser power is required. There will not be quenching of fluorescence compared to previous techniques, as no IR was used.…”
Section: Optical Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its use in crop protection is just in its early days. [1] Nanoparticles or nanomaterials are substances of nanometer sizes (generally between 1 and 100 nm). Over many decades, nanotechnology and nanomaterials have been employed successfully and safely in various fields like medicine, environmental science, and agriculture.…”
Section: Introductionmentioning
confidence: 99%